Pengembangan LKPD Berbasis Kontekstual Untuk Meningkatkan Kemampuan Representasi Matematis Peserta Didik Pada Materi Trigonometri - Riana Sari; Arini Yanfauni; Rizki Wahyu Yunian Putra; Abi Fadila (Lembaga Bale Literasi, 2025)
This study uses the research and development (R&D) method with the ADDIE model (analysis, design, development, implementation, and evaluation), the subjects of this study were students of class X of SMK PGRI 4 Bandar Lampung. The techniques used in collecting data were interviews, validation questionnaires, and product and test attractiveness questionnaires. The results of the study showed that the assessment obtained by media experts was 0.83 with very high criteria and material experts 0.88 with very high criteria. While the response of small group students was 4.5 with interesting criteria and large group trials were 4.34 with very interesting criteria. And the results of the effectiveness test obtained an n-gain effectiveness score of 0.85 with high criteria and in the form of a percentage of 85% which means it is effective for use in learning.